The Effect of Body Posture on Brain Glymphatic Transport - Hyun Joo Lee; L. Xie; Mei Yu; Hyekyung Kang; Feng Tian; Rashid Deane; Jean Logan; M. Nedergaard; Helene Benveniste (2015)
The glymphatic pathway expedites clearance of waste, including soluble amyloid β (Aβ) from the brain. Transport through this pathway is controlled by the brain9s arousal level because, during sleep or anesthesia, the brain9s interstitial space volume expands (compared with wakefulness), resulting in faster waste removal. Humans, as well as animals, exhibit different body postures during sleep, which may also affect waste removal. Therefore, not only the level of consciousness, but also body posture, might affect CSF–interstitial fluid (ISF) exchange efficiency. We used dynamic-contrast-enhanced MRI and kinetic modeling to quantify CSF-ISF exchange rates in anesthetized rodents9 brains in supine, prone, or lateral positions. To validate the MRI data and to assess specifically the influence of body posture on clearance of Aβ, we used fluorescence microscopy and radioactive tracers, respectively. The analysis showed that glymphatic transport was most efficient in the lateral position compared with the supine or prone positions. In the prone position, in which the rat9s head was in the most upright position (mimicking posture during the awake state), transport was characterized by "retention" of the tracer, slower clearance, and more CSF efflux along larger caliber cervical vessels. The optical imaging and radiotracer studies confirmed that glymphatic transport and Aβ clearance were superior in the lateral and supine positions. We propose that the most popular sleep posture (lateral) has evolved to optimize waste removal during sleep and that posture must be considered in diagnostic imaging procedures developed in the future to assess CSF-ISF transport in humans. SIGNIFICANCE STATEMENT The rodent brain removes waste better during sleep or anesthesia compared with the awake state. Animals exhibit different body posture during the awake and sleep states, which might affect the brain9s waste removal efficiency. We investigated the influence of body posture on brainwide transport of inert tracers of anesthetized rodents. The major finding of our study was that waste, including Aβ, removal was most efficient in the lateral position (compared with the prone position), which mimics the natural resting/sleeping position of rodents. Although our finding awaits testing in humans, we speculate that the lateral position during sleep has advantage with regard to the removal of waste products including Aβ, because clinical studies have shown that sleep drives Aβ clearance from the brain.